Isolation and cultivation of freshwater microalgae for biopharmaceutical applications / Nur Farahanim Mohd Tahir - Mohd Tahir, Nur Farahanim (2014)
Microalgae are currently being study widely. This research is conducted to isolate microalgae from :freshwater and explore their bioactive compounds that have potential for biopharmaceutical application. Twenty-two indigenous microalgae samples from Malaysia freshwater microalgae originated from ponds of Silo Agropark, Temoh, Perak (4°14'0"N, 101 °10'0"E) and Universiti Teknologi Mara, UiTM Puncak Alam (3°12'12''N, 101 °27'10"E) were collected. The samples have been subjected to four different regimes to isolate the microalgae from the fresh water samples. The regimes were conducted to study the culturing in broth and centrifugation steps prior to culture onto TAP agar. Regimes 3 and 4 yield the highest percentage microalgae recovery of 40% from KU samples and 71 % from PA pond. To isolate more microalgae, all the regimes must be conducted even though Regime 1 and 2 were not applicable to KU pond, it had yield about 29% to 57% microalgae recovery from PA pond. Under prolonged and repeated subculturing in vitro on Tris Acetate Phosphate (TAP) media, severe contamination remained. Therefore, wide spectrum of antibiotic such as ampicillin was selected to resolve this problem. The microalgae have been exposed with 0.5 g/L of ampicillin in TAP broth at different time of exposure (12, 24, 36 and 48 hours) and have been cultured onto TAP agar containing different concentration of ampicillin (0, 0.5, 0.75 and 1.0 g/L). Microscopic observation shows the diversity of morphology of the microalgae with most of the microalgae have sphere shape and other like oblong shape with diameter in range of 50 to 280 µm. Extraction of microalgae was done to extract the bioactive compound and was analyzed using high performance liquid chromatography (HPLC). However, no UV active compounds have been detected using HPLC method and further study need to be conducted to explore the bioactive compound in the microalgae.